Revalidation, synonymies, and notes in American Callichromatini (Coleoptera, Cerambycidae, Cerambycinae) - Santos-Silva, Antonio; Schmid, Herbert (Zootaxa, 2021)
The unpublished formal synonymy of Callichroma chiriquina Bates, 1879, C. opiparum Bates, 1874, C. compressipes Casey, 1912, and C. regalis Casey, 1912 is commented. Schwarzerion carinatum Schmidt, 1924 is removed from the synonym of Callichroma holochlorum holochlorum Bates, 1872, and transferred to the synonymy of Callichroma euthalia Bates, 1879. The species group name “euthalium” is corrected. The type-localities of Schwarzerion carinatum are reported as Colombia and West Indies, and the institution where one of the syntypes is deposited is corrected. Callichroma collarti Fuchs, 1959 is revalidated, and Callichroma magnificum Napp & Martins, 2009 is considered its junior synonym. The status of the specimens of the type series of Callichroma collarti is commented. Additionally, the holotype of Callichroma opiparum Bates, 1874, and the lectotype of Callichroma chiriquina Bates, 1879 are illustrated for the first time.